Carnival catastrophe - Lloyd, Natalie (Katherine Tegen Books, an imprint of HarperCollins Publishers, 2020)
All siblings are capable of magic if they stick together. But trusting each other isn't easy for the Problim siblings when neighbors like Desdemona and Carly-Rue O'Pinion are working double-time to turn the town against them. From catapulting cattle to runaway corndogs to spiders on the pageant stage, the Problim brothers and sisters are blamed for every catastrophe at this year's carnival. And to top it all off, Mama Problim is missing! Can the seven siblings come together in time to save the carnival and rescue their mom from a villain even more dastardly than Desdemona? Or will they discover too late what it truly means to be a Problim?